The Influence of Entrepreneurial Motivation, Entrepreneurial Learning, and Use of Social Media on Entrepreneurial Interest in The Community - Basuki Suko (Greenation Research & Yayasan Global Resarch National, 2023)
This research aims to determine how big the influence is between independent variables such as entrepreneurial motivation and entrepreneurial interest, entrepreneurial learning, and entrepreneurial interest, and the use of social media and entrepreneurial interest. This research was conducted using quantitative methods and explanatory research. This research uses a purposive sampling technique. Questionnaires and documentation are used for research. The distribution questionnaire was used to measure the relationship between the independent variables, namely entrepreneurial learning, entrepreneurial motivation, and use of social media, and the dependent variable, namely entrepreneurship in the community. Each respondent received a questionnaire via WhatsApp online. SmartPLS 3.0 software was used to perform data analysis using structural equation modeling (SEM). Previous research has tested the instrument used in this research on 30 respondents, and the results show that the instrument is valid and reliable. Validity and reliability tests, uniform normality, and hypotheses are the data analysis methods used in this research.